Burden of influenza in patients with cardiovascular disease who receive antiviral treatment for influenza. (31st December 2022) - Corral, Mitra; Castro, Rita de Cassia; To, Tu My; Arndorfer, Stella; Wang, Shu; Stephens, John
Abstract: Aims: Cardiovascular disease (CVD) increases the risk of complications from respiratory viruses, including influenza. Moreover, respiratory viruses may increase the risk of CV events. Antiviral medication may reduce healthcare resource utilization (HRU), but more data is needed in CVD populations to explore relationships between influenza antiviral treatment, CVD-related complications, HRU, and costs. Materials and methods: This retrospective claims analysis examined data extracted from IBM MarketScan Commercial Claims and Encounters and Medicare Supplemental and Coordination of Benefits databases during three influenza seasons: 2016–2017, 2017–2018, or 2018–2019. Propensity score matching was used to compare HRU outcomes and costs among CVD patients treated with influenza antivirals and untreated patients. Results: Across all influenza seasons, patients with CVD and influenza who received antiviral treatment had fewer all-cause emergency department (ED) visits ( p  < .01), respiratory-related HRU ( p  < .01), respiratory-related outpatient and ED visits (both p  < .01), CVD-related HRU ( p  < .01), heart failure-related HRU visits ( p  < .01), and kidney failure-related HRU ( p  < .01) 180 days post-treatment fill date than CVD patients untreated for influenza. CVD patients treated with antivirals also had a lower mean number of all-cause inpatient, outpatient, and ED visits and days of stay (all p  < .01) and fewer mean respiratory-related outpatient and ED visits (both p  < .01). HRU patterns were generally consistent over time and across individual influenza seasons. Finally, treated CVD patients incurred lower all-cause outpatient costs 180 days post-treatment fill date ( p  < .05) than CVD patients untreated for influenza. Conclusion: CVD patients who contract influenza and take antiviral medication have fewer short- and long-term influenza-related complications and less overall HRU compared with CVD patients who were not prescribed antiviral treatments. Antiviral treatment may be an important tool in reducing complications in CVD patients with influenza. PLAIN LANGUAGE SUMMARY: People with heart disease are more likely to have complications from respiratory viruses, including influenza (flu). Moreover, respiratory viruses may increase the risk of damage to the heart muscle. We examined whether patients with heart disease who get the flu and take prescription medications called antiviral drugs have fewer short- and long-term flu-related complications and use fewer healthcare services than patients with heart disease who do not take antiviral drugs. We examined commercial and Medicare databases during three influenza seasons (2016–2017, 2017–2018, and 2018–2019), and we compared outcomes and costs among heart disease patients who were treated or not treated with antiviral drugs. Patients with heart disease and the flu who received antiviral drugs had fewer visits to the emergency room, used fewer healthcare services for respiratory-related problems, used fewer heart disease-related healthcare services, and had fewer heart failure-related or kidney failure-related healthcare visits than heart disease patients who were not treated for the flu. Finally, patients with heart disease who were treated with antiviral drugs spent less money on outpatient services than patients with heart disease who were not treated with antiviral drugs. We determined that patients who get the flu and take antiviral drugs have fewer short- and long-term flu-related complications and use fewer healthcare services than heart disease patients who do not receive antiviral drugs. Therefore, it may be important to treat heart disease patients with antiviral drugs in order to reduce the number of flu-related complications in these patients.